Optimization of irrigation and fertilization of apples under magnetoelectric water irrigation in extremely arid areas - Duan, Xiaoxian; Wang, Quanjiu; Mu, Weiyi; Wei, Xuesong (Frontiers in Plant Science, 2024)
Abstract Apple (Malus pumila Mill.) is one of the important economic crops in the arid areas of Xinjiang, China. For a long time, there has been a problem of high consumption but low yield in water and fertilizer management, prevent improvements in apple quality and yield. In this study, 5-year-old ' Royal Gala ' apple trees in extremely arid areas of Xinjiang were used as experimental materials to carry out field experiments. considering 5 irrigation levels (W1, 300 mm; W2, 425 mm; W3, 550 mm; W4, 675 mm; W5, 800 mm) and 5 fertilization levels (F1, 280 kg·ha-1; F2, 360 kg·ha-1; F3, 440 kg·ha-1; F4, 520 kg·ha-1; F5, 600 kg·ha-1) under magnetoelectric water irrigation conditions. This study aimed to explore the mode of combining magnetoelectric water irrigation and water and fertilizer coupling optimization management for high-quality-yield apple. The results demonstrated that magnetoelectric water combined with the application of 675 mm irrigation amount and 520 kg·ha-1 fertilization amount was the most effective combination. These results occurred by increasing net photosynthetic rate of apple leaves，improved the quality of apples, increased apple yield, and promoted the improvement of water and fertilizer use efficiency. The synergistic effect of water and fertilizer has a positive effect on optimizing apple water and fertilizer management. Additionally, the quadratic regression model was used to fit the response process of yield, IWUE and PFP to irrigation amount and fertilization amount, and the accuracy was greater than 0.8, indicating good fitting effects. The magnetoelectric treatment combined water and fertilizer mainly affected apple yield, water and fertilizer use efficiency and vitamin C content related to quality. The highest comprehensive score of W4F4 treatment was 2.67, which was identified as the optimal water and fertilizer treatment. This study provides valuable guidance for improving water and fertilizer productivity, crop yield and quality in extreme arid areas of Xinjiang by using magnetized and de-electronic water irrigation.